2017
DOI: 10.1161/jaha.117.006302
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight, Postnatal Weight Gain, and Childhood Adiposity in Relation to Lipid Profile and Blood Pressure During Early Adolescence

Abstract: BackgroundDifferent pathways likely underlie the association between early weight gain and cardiovascular disease risk. We examined whether birth weight for length relationship and weight gain up to 2 years of age are associated with lipid profiles and blood pressure (BP) in early adolescence and determined whether childhood adiposity mediates these associations.Methods and ResultsData from QUALITY (Quebec Adipose and Lifestyle Investigation in Youth), a cohort of white children with parental history of obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…In agreement with some 9,28,31 but not all 72 prior investigations, we found a statistically significant association between birth weight and childhood HDL (positive), and TG (negative). Inclusion of the child's current BMI strengthened these associations.…”
Section: Lipidssupporting
confidence: 93%
“…In agreement with some 9,28,31 but not all 72 prior investigations, we found a statistically significant association between birth weight and childhood HDL (positive), and TG (negative). Inclusion of the child's current BMI strengthened these associations.…”
Section: Lipidssupporting
confidence: 93%
“…An increase in [33]. Other studies have found rapid weight gain early in childhood to be associated with cardiometabolic risk factors in later childhood [34,35]. These findings suggest that a child presenting with an increase in zBMI over time may need to be monitored for the development of cardiometabolic risk factors, even when the BMI values remain below the age and sex-adjusted cutoff for overweight.…”
Section: Discussionmentioning
confidence: 83%
“…However, some studies have showed little effect of LBW on blood pressure in young adults [9,10]. On the other hand, some recent studies suggest that the co-existence of low birthweight and later obesity, rather than low birthweight itself, was a strong risk factor of HBP during adolescence [11,12,13,14,15,16,17]. The relationship between LWB and HBP remains unclear, and obesity during school-age is seldom brought into consideration.…”
Section: Introductionmentioning
confidence: 99%